Implementasi Budaya Sekolah dalam Meningkatkan Kualitas Perilaku Siswa di Madrasah Aliyah Ghozaliyah Jogoroto Jombang - habibah, aenun (Nurul Jadid University, Paiton Probolinggo, East Java, 2021)
Abstract- The purpose of this study is to determine the implementation of school culture in improving the quality of student behaviour in the Madrasah Aliyah Al-Ghozaliyah jogoroto Jombang, this study used qualitative methods of field is descriptive, the type of research used is the case study. Based on the results of the study showed that the implementation of school culture in improving the quality of student behaviour in the Madrasah Al-Ghozaliyah Jogoroto Jombang such as the following: 1) the presence of extracurricular activities as a means of shaping the character of students 2) completing activities of Al-Quran to improve the attitude of the spiritual students , 3) the inhibiting factors there are on the personal students while the factors supporting the cooperation of teachers. Keywords- School Culture, Behavior